Quo vadis, Journalism degree? Job placement, labour market, and the training of Journalism graduates - Martínez-Nicolás, Manuel (Anuario ThinkEPI, 2023)
The gradual decline in tuition and in the access qualifications or the low satisfaction of graduates are some of the indicators that point to a situation which, if not alarming, is at least worrying about the state of university studies in Journalism in Spain. The retraction of the labour market with the cycle of economic crisis that began in 2008 and the impact of digitalisation in the sector make it difficult for the Bachelor’s Degree in Journalism to meet the objective of employability-oriented training that the Bologna Declaration (1999) placed at the centre of the reform of higher education in the European Union. The difficulties generated by these exogenous factors are being reinforced by the curricular design of a degree anchored in a strictly “media-based” conception of journalistic activity and in the transmission of a “journalistic ideal” that graduates are unable to put into practice when they enter the job market that is actually available to them.